Therapeutic Letters in Counselling Practice: Client and Counsellor Experiences - Pyle, Nathan R. (Canadian Journal of Counselling and Psychotherapy, 2007)
Therapeutic letter writing as an adjunct to counselling has increased in use by counsellors in the last decade. Despite this growth, limited research attention has been devoted to how clients interpret such documents. This study investigated the letter-writing practices of a small group of counsellors as well as the experiences of seven clients who had received a letter from their counsellors during therapy. The data collected and analyzed were in the form of letters written by clients to the researcher. Four themes emerged from the analysis of their letters: (a) curiosity and connection, (b) consolidation: relationships and session content, (c) facilitating and hindering, and (d) in perpetuity: the tangible and lasting presence of letters. Implications for counselling and future research are discussed.